Urban delineation through a prism of intraday commute patterns - Bogomolov, Yuri; Belyi, Alexander; Sobolevsky, Stanislav (Frontiers in Big Data, 2024)
Drawing upon the wealth of information contained in passive mobile phone data, this study delves into the intricate dynamics of urban mobility patterns in Brno, Czech Republic, offering valuable insights for urban and transportation planning. Our methodological advancement incorporates bidirectional commute flows and integrates urban and suburban commute networks within a unified framework, comprehensively representing the city's mobility landscape. We uncover consistent structural features by employing clustering techniques to identify distinct mobility patterns, including a central business district, residential communities, and an intermediate hybrid cluster. These findings underscore the practical utility of intraday mobility insights in informing transportation planning decisions and optimizing infrastructure utilization. The study's findings demonstrate the remarkable potential of passive mobile phone data to provide granular insights into urban mobility patterns, paving the way for more effective and efficient transportation planning strategies.